Is Dividend Payment of any Influence to Corporate Performance in Nigeria? Empirical Evidence from Panel Cointegration - Rafindadi, Abdulkadir Abdulrashid; Bello, Abdulrashid (International Journal of Economics and Financial Issues, 2019)
Firms are established objectively to maximize their value and that of their shareholders; this can be achieved via payment of dividend and investment in profitable ventures. Studies conducted in both developed and developing economies could not solve the problem of dividend dynamism. It is against this background that this study is conducted to determine the effect of firms’ performance on dividend policy of 11 listed financial companies in Nigeria purposively selected for a period of twenty years (1997 – 2016). Secondary data was collected and used for analysis. Hausman and Wald test were conducted to choose between fixed effect and random effect, and fixed and Pooled OLS respectively. The study conducted correlation matrix test, panel unit root and panel cointegration test while all study objectives were tested using multiple regression of the fixed effect analysis. The outcome from the regression reveals that all the independent variables significantly affect dividend payout ratio of the sampled companies. It is clear from the analysis that performance affects dividend decisions in both short and long runs. As such, managers of these companies should sustain effective utilization of their assets and should also strive to increase the value of their equity by investing larger portion of their earnings into profitable ventures. Keywords: Performance, dividend policy, financial sector, Accounting based measures, Market based measures, Tobin’s Q, Market value added JEL Classificiations: G3, M41 DOI: https://doi.org/10.32479/ijefi.7601